"Building Your Neurology Acumen": A Flipped Classroom Approach for Internal Medicine Residents. (25th May 2023) - Zaeem, Zoya; Smyth, Penelope; King, Sharla; Daniels, Vijay J.
ABSTRACT: Globally, internal medicine (IM) residents often feel they lack the knowledge and skills to approach patients presenting with neurologic issues. We conducted a multiple method needs assessment to determine the feasibility of a novel neurology flipped classroom (FC) curriculum for internal medicine residents. Our primary findings include participants: (1) finding neurology a useful rotation; (2) feeling uncomfortable with the neurological examination; and (3) endorsing flipped classroom as a potential alternative but with significant barriers. Our findings elucidate upon the various extrinsic/intrinsic motivators for resident education and illustrate the need to re-examine the way in which neurology is being taught to off-service residents.